2019
DOI: 10.1021/acsearthspacechem.8b00177
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Ozonolysis of Endocyclic Unsaturated Organic Aerosol Proxies: Implications for Criegee Intermediate Dynamics and Later-Generation Reactions

Abstract: Unsaturated low-volatile organic compounds have been observed in atmospheric aerosol particles (e.g., aerosols from plants, cooking, and biomass burning) and human skin. Understanding their chemical fates through reactions with ozone at the relevant interfaces is crucial to elucidating the multiphase chemical mechanisms and predicting their environmental and health impacts. In this work, heterogeneous ozonolysis of two endocyclic unsaturated organic aerosol proxies (4-cyclohexene-1,2-diacid and shikimic acid) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 73 publications
(114 reference statements)
5
35
0
Order By: Relevance
“…The density of erythritol particles is estimated to be 1.173 g cm −3 , using the volume additivity rule with the density of water and erythritol (1.451 g cm −3 ) and particle composition (i.e., mass fraction of solute, mfs). The mfs is derived from the hygroscopicity data reported by Marsh et al 2017and is reported to be 0.47±0.02 at 85 % RH, which agrees well with model simulations (mfs = 0.482) using the Aerosol Inorganic-Organic Mixtures Functional groups Activity Coefficients (AIOMFAC) model (Zuend et al, 2008(Zuend et al, , 2011. For erythritol-AS particles, the particle diameters were measured to be 278.2-281.5 nm before oxidation (Table 1).…”
Section: Oxidation Kinetics Of Erythritol and Erythritol-as Particlessupporting
confidence: 79%
“…The density of erythritol particles is estimated to be 1.173 g cm −3 , using the volume additivity rule with the density of water and erythritol (1.451 g cm −3 ) and particle composition (i.e., mass fraction of solute, mfs). The mfs is derived from the hygroscopicity data reported by Marsh et al 2017and is reported to be 0.47±0.02 at 85 % RH, which agrees well with model simulations (mfs = 0.482) using the Aerosol Inorganic-Organic Mixtures Functional groups Activity Coefficients (AIOMFAC) model (Zuend et al, 2008(Zuend et al, , 2011. For erythritol-AS particles, the particle diameters were measured to be 278.2-281.5 nm before oxidation (Table 1).…”
Section: Oxidation Kinetics Of Erythritol and Erythritol-as Particlessupporting
confidence: 79%
“…The extraction procedures follow previous studies. 30,35,42 From the GC−MS measurements, four major α-pinene SOA tracers were detected and quantified, including pinonic acid (C 10 H 16 O 3 ), cis-pinic acid (C 9 H 14 O 4 ), 10-hydroxypinonic acid (C 10 H 16 O 4 ), and 3-hydroxyglutaric acid (C 5 H 8 O 5 ) ( Figure S2). 43,44 From the detailed IMS-TOF measurements under both the positive and negative ion modes, we observed a number of polar oxygenated compounds with chemical formulas consistent with previously reported α-pinene SOA monomeric and dimeric products.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…38 SOA Compositions Measured by Offline Mass Spectrometry Techniques. Portions of the SOA filter samples were extracted for offline analyses by a gas chromatograph electron impact ionization mass spectrometer (GC−MS, Agilent Inc. 7890 GC and 5975 MSD) 35 and an electrospray ionization (ESI) ion mobility spectrometry timeof-flight mass spectrometer (IMS-TOF, Tofwerk Inc.) 39−41 to study the molecular compositions of the resultant SOA. The extraction procedures follow previous studies.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…11,12 HHPs are recently detected by APCI-MS/MS to study the SOA. 41,42 In situ detection of hydroperoxides suggests the oxidizing capacity of the aqueous surface exists even without UV light. The high Henry's law constant indicates that the HHPs has a high potential to partition into the aqueous phase, 43 further facilitating the uptake of VOCs and other trace gases onto the aqueous surface of clouds, fogs, or wet aerosols.…”
Section: Temporal Evolution Of Dark-aging Productsmentioning
confidence: 99%